Stimulant Induced Trichotillomania in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The onset or exacerbation of trichotillomania (TT) within 6 months of starting treatment with methylphenidate (dose unreported) for ADHD is reported in 3 boys, aged 7 to 12 years, followed at the Yale Child Study Center, New Haven, CT.